AUTOMATED MEASUREMENT SYSTEM OF THE CURVATURE OF THE RAIL TRACK BASED ON GYRO - Kukhlyvskyi, S. V.; Kupras, V. M.; Bondarenko, B. M. (Science and Transport Progress, 2007)
Offered automated system of measuring of curvature of railway way on the basis of gyroscope, including with the use of modern laser gyroscopes. It is suggested to use a circular laser gyroscope (СLG), so-called quantum gyroscope created on the basis of laser with a circular resonator, in which on the reserved optical contour electromagnetic head-seas spread simultaneously. To dignities of laser gyroscopes it is necessary to deliver absence of the revolved rotor and bearings creating force of friction foremost, and also high exactness of measuring.